Vaginal birth after cesarean section: Experience from a regional hospital - Yi Ting Chen (Taiwanese Journal of Obstetrics & Gynecology, 2022)
Objective: Trial of labor after cesarean section (TOLAC) is an option for women with previous cesarean section. However, few women choose this option because of safety concerns. We evaluate the safety and risks associated with TOLAC and the success rate of vaginal birth after cesarean delivery (VBAC). Material and methods: We reviewed all patients with a history of previous cesarean section that underwent elective repeat cesarean section (ERCS) or TOLAC in a regional teaching hospital from Nov, 2013 to May, 2018. Maternal basic clinical information, intrapartum management, postpartum complications, and neonatal outcomes were analyzed. Results: 199 pregnant women with a history of at least one previous cesarean section were enrolled. 156 women received ERCS and 43 women (21.6%) underwent TOLAC, with 37 (86.0%) who underwent successful VBAC. The VBAC rate was 18.6%. Higher success rate was found in women with previous vaginal birth than in women without vaginal birth (100% vs. 81.8%). One case (2.3%) in the VBAC group was complicated with uterine rupture and inevitable neonatal death during second stage of labor. The uterus was repaired without maternal complications. In another case, the newborn's condition was complicated with low APGAR score (<7) at birth due to maternal chorioamnionitis. Among indications for previous cesarean section, cephalo-pelvic disproportion (CPD) was associated with TOLAC failure and uterine rupture after VBAC. Conclusion: VBAC is a feasible and safe option. Modes of delivery should be thoroughly discussed when considering TOLAC for women with history of previous cesarean section due to CPD, considering its association with TOLAC failure in second stage of labor.